Price, credit or ambiguity? Increasing small-scale irrigation in Ethiopia. (March 2023) - Balasubramanya, Soumya; Buisson, Marie-Charlotte; Mitra, Archisman; Stifel, David
Highlights: Support for groundwater irrigation in Ethiopia focuses on easing pump purchases while considerable ambiguity exists around well drilling. A discrete choice experiment (DCE) is used to assess farmers' willingness to adopt smallholder private irrigation packages. Access to loans and reduced well drilling ambiguities have the greatest effect on the probability of adopting irrigation packages. Lowering pump prices has the smallest effect on the adoption of irrigation packages. An essential and cost-effective step toward expanding groundwater irrigation in Ethiopia is the reduction of ambiguities around well drilling. Abstract: Governments in countries in Sub-Saharan Africa (SSA) are keen to expand irrigation to improve food security and are placing particular emphasis on adoption and use of smallholder private groundwater irrigation. Yet private irrigation is a multi-stage technology, the adoption of which is affected by fiscal support and extension services offered on different investment stages but also by uncertainties around actions that need to be undertaken in these stages. Groundwater-based irrigation in Ethiopia presents a case where policy has focused on fiscally easing the purchase of pumps while considerable ambiguity (unquantifiable uncertainty) exists around the outcomes of drilling boreholes (reaching water). In this paper, we examine farmers' willingness to adopt smallholder private irrigation packages in response to lower pump prices following tax breaks, loan availability, and reduction in ambiguities related to borehole drilling, using a discrete choice experiment (DCE) in two districts of Ethiopia. The results indicate that the provision of loans and reduction in ambiguities related to well drilling have the greatest effect on the probability of farmers adopting irrigation packages. Lowering pump prices has the smallest effect. Pump-type has a small effect, with energized pumps preferred over manual ones. In exploring heterogeneity in preferences, we find that farmers without irrigated plots and those with greater market access have a greater preference for the provision of loans, while those with greater market access also have greater preferences for reductions in well drilling ambiguities. The results of this choice experiment suggest that reducing ambiguities around well drilling (initial investments) is an essential and cost-effective step toward expanding groundwater-based irrigation in Ethiopia.